New beginnings - Brooke, Lauren (New York : Scholastic, 2004)
Amy visits her friend Carey and at first assumes that Carey needs help with her unruly horse Mustang. Later, Amy wonders why Carey is surprisingly cold towards both her and the horse.
"A working partners series"- -P. [4] of cover.
G6
Keywords: Animal welfare -- Juvenile fiction; Horses -- Training -- Juvenile fiction; Friendship -- Juvenile fiction; Horse farms -- Juvenile fiction; Heartland (Va. : Imaginary place) -- Juvenile fiction; Animals -- Treatment -- Fiction; Horses -- Training -- Fiction; Friendship -- Fiction; Horse farms -- Fiction; Heartland (Va. : Imaginary place) -- Fiction; Virginia -- Juvenile fiction; Virginia -- Fiction